New Insights into Congenital Diaphragmatic Hernia – A Surgeon’s Introduction to CDH Animal Models - Chiu, Priscilla Pui Lam (Frontiers in Pediatrics, 2014)
In recent decades, new research into the developmental defects and pathophysiological basis of congenital diaphragmatic hernia has revealed opportunities for the development of innovative therapies. Importantly, the use of animal models to represent this anomaly in the laboratory has resulted in the discovery of many important genetic, epigenetic and other molecular contributors to this condition. In this review, the most commonly used and newly devised animal models of CDH are presented to familiarize the reader with the latest innovations in the basic sciences.